2005
DOI: 10.1080/01612840590901699
|View full text |Cite
|
Sign up to set email alerts
|

Divorce Transition Differences of Midlife Women

Abstract: Divorce transition experienced by and its influence upon midlife women's health is not fully understood. Interviews were conducted with 24 divorced women who self-classified into decider status groups: initiator (who first decided to end marriage), non-initiator (recipient of end of marriage decision), and mutual decider (shared decision to end marriage). Interpretive content analysis involving pattern coding was conducted. The divorce transition by initiators (n=8) included self-focused growth, optimism, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 41 publications
4
25
0
Order By: Relevance
“…Nevertheless, the magnitude of the adverse outcomes produced by divorce can be buffered or exacerbated by some moderator variables, such as divorce initiator status, career status, and existence of a new intimate relationship (Sakraida, 2005;Wang & Amato, 2000). More concretely, divorce initiator status is highlighted as one of the most robust moderators of the enhancement of quality of life after the marital dissolution (Wallerstein, 1986).…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the magnitude of the adverse outcomes produced by divorce can be buffered or exacerbated by some moderator variables, such as divorce initiator status, career status, and existence of a new intimate relationship (Sakraida, 2005;Wang & Amato, 2000). More concretely, divorce initiator status is highlighted as one of the most robust moderators of the enhancement of quality of life after the marital dissolution (Wallerstein, 1986).…”
Section: The Present Studymentioning
confidence: 99%
“…More concretely, divorce initiator status is highlighted as one of the most robust moderators of the enhancement of quality of life after the marital dissolution (Wallerstein, 1986). Past research with individuals who had divorced, separated, or dissolved a nonmarital relationship consistently revealed that noninitiators of the relationship dissolution reported more psychological distress, more psychosomatic symptoms, and they perceived the dissolution as more stressful (Davis, Shaver, & Vernon, 2003;Sakraida, 2005;Wang & Amato, 2000). Noninitiators reported more often feelings of shock with the end of the relationship, lower levels of emotional recovery, as well as a worse sense of event controllability and more emotional attachment to the ex-partner (Davis et al, 2003;Frazier & Cook, 1993).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Sakraida (2005) found that midlife women initiators of divorce shared self-focused growth, optimism, and loss of social support and opportunities. Some women may feel a sense of freedom and have opportunities to explore new challenges that they might otherwise not have sought.…”
mentioning
confidence: 97%
“…The women's experience of being neglected and treated with derision was striking. Although studies of White divorced women conducted in the 1990s and earlier in the United States mention social stigma being imposed on divorced women, (Radford et al, 1997;Sakraida, 2005), stigma appears to be less important in more recent studies. But social disapproval and prejudice of divorced individuals and their children continue to be important in studies of Korean women's adjustment after divorce in the U.S. and in Korea (Kim, Park, & Choi, 2010;Lee & Bell-Scott, 2009;Whang, 2007;Yang, 1999).…”
Section: Discussionmentioning
confidence: 99%